Child Sexual Abuse Allegations: Challenges Faced by Social Workers in Child Protection Organisations. Issue 5 (20th October 2017) - Schiller, Ulene
Abstract : Social workers employed in Child Protection Organisations (CPOs) are frequently confronted with child sexual abuse cases. This paper aims to determine the challenges faced by social workers employed by CPOs when dealing with allegations of child sexual abuse. A qualitative study was done using focus group discussions with 71 social workers as participants. The social developmental welfare approach and legislative mandates were used to analyse the research problem of challenges that social workers experience when dealing with allegations of child sexual abuse allegations. The findings indicate that existing South African policies, conventions and legislation do not always complement each other, but rather create challenges and uncertainties amongst social workers in this field. This, together with insufficient resources for service delivery, often leads to re-victimisation of the child who has been sexually abused. This paper concludes with recommendations based on the social developmental principles that suggest integrated and collaborative partnerships to ensure effective responses to child sexual abuse cases. Secondly, it urges universities to relook their curricula to ensure sufficient training for undergraduate social worker students takes place to deal with sexual abuse allegations.